2022
DOI: 10.3389/fnsyn.2021.804898
|View full text |Cite
|
Sign up to set email alerts
|

Blast-Induced Mild Traumatic Brain Injury Alterations of Corticotropin-Releasing Factor Neuronal Activity in the Mouse Hypothalamic Paraventricular Nucleus

Abstract: Blast-induced mild traumatic brain injury (mbTBI) is the most common cause of TBI in US service members and veterans. Those exposed to TBI are at greater risk of developing neuropsychiatric disorders such as posttraumatic stress disorder, anxiety and depressive disorders, and substance use disorders following TBI. Previously, we have demonstrated that mbTBI increases anxiety-like behaviors in mice and dysregulates stress at the level of corticotropin-releasing factor (CRF) neurons in the paraventricular nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Up to 30% of TBI patients experience neuroendocrine dysfunction [41][42][43][44] with a high incidence of HPA axis dysregulation 42,44 . Hypothalamic and extra-hypothalamic CRF systems are also responsive to mTBI injuries and have significant impact on stress-related neuronal responses and affective states following mTBI [45][46][47][48][49] . The mouse LHb shows immunoreactivity and mRNA expression for both CRF and CRFR1 69,70 , and receives inputs from the structures that contain CRF neurons including the paraventricular nucleus of hypothalamus (PVN) and the extrahypothalamic CRF system such as the bed nucleus of stria terminalis (BNST) 71 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 30% of TBI patients experience neuroendocrine dysfunction [41][42][43][44] with a high incidence of HPA axis dysregulation 42,44 . Hypothalamic and extra-hypothalamic CRF systems are also responsive to mTBI injuries and have significant impact on stress-related neuronal responses and affective states following mTBI [45][46][47][48][49] . The mouse LHb shows immunoreactivity and mRNA expression for both CRF and CRFR1 69,70 , and receives inputs from the structures that contain CRF neurons including the paraventricular nucleus of hypothalamus (PVN) and the extrahypothalamic CRF system such as the bed nucleus of stria terminalis (BNST) 71 .…”
Section: Discussionmentioning
confidence: 99%
“…TBI patients also experience neuroendocrine dysfunction 4144 with dysregulation of the hypothalamic pituitary axis (HPA) stress neuromodulator, corticotropin releasing factor (CRF), that has significant impact on stress neuronal responses and affective states following mTBI 4549 . Our previous studies have demonstrated that the rodent LHb is highly responsive to CRF 50, 51 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation